EFEKTIFITAS PEMBERIAN MASSAGE DENGAN RECOVERY AKTIF TERHADAP PENURUNAN DENYUT NADI PADA ATLET BOLA VOLI PUTRA UNGGA ELEKTRIK - Zakir Burhan (LPPM Institut Pendidikan Nusantara Global, 2021)
Massage is a manipulation of soft tissue structures that are applied to the human body to create a sense of calm, comfort, relaxation, and reduce pain. The purpose of this study was to determine whether or not the effectiveness of giving massage with active recovery to the decrease in pulse rate in the Putra Ungga Electric volleyball athletes in 2020. This study used an unpaired t test, also commonly referred to as a different sample t test because the distribution of the data compared come from two different groups. The research sample was 20 people. The results of the analysis of the effectiveness of giving massage the average pulse rate of 150 are greater when compared to active recovery which has an average pulse value of 120, so that the results of giving massage with active recovery have the same slight difference in effectiveness. The result of the t calculation based on the above formula is the t count which is 2.163 which is compared to the t table at a significant level of 5% at the degrees of freedom (df = N-1) = (10-1 = 9) which is 1.833. From these results, it can be concluded that there is an effectiveness of giving massage with active recovery to decrease pulse rate in the Putra Ungga Electric volleyball athletes in 2020 and the null hypothesis that the author proposes (Ha) is accepted because t-count > t-table (2.163 > 1833).